Sustainable Technologies for Nearly Zero Energy Buildings Design and Evaluation Methods - Medved, Sašo.; Domjan, Suzana; Arkar, Ciril; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents cutting-edge work on the energy efficiency and environmental sustainability of buildings, examining EU policies, regulations and technologies for complex systems such as passive buildings, sustainable buildings and, as part of the Energy Performance of Building Directive (EPBD), nearly Zero Energy Buildings (nZEB) requirements. It explores a wide range of topics, including indoor environment requirements, building physics, in-situ experiments to determine the thermal properties of buildings, nZEB requirements, building service technology, and methods of evaluating energy efficiency and environmental impacts. It also provides an overview of the best available technologies for nZEB, including those for the rational use of energy, utilization of renewable energy sources, EPBD systems and calculation methods. This book is a valuable resource for students, researchers and practitioners of urban planning, and architecture, civil and mechanical engineering.
Indoor comfort requirements -- Energy sources -- Introduction to building physics -- Experimental evaluation of buildings' envelope thermal properties -- Global climate and energy performance of the building -- Best available technologies (BAT) for on-site and nearby generation of heat for nZEB -- Best available technologies (BAT) for on-site electricity generation for nZEB -- Space heating of nZEB -- Space cooling of nZEB -- Domestic hot water heating in nZEB -- Ventilation of nZEB -- Energy efficient lighting of nZEB -- Energy labelling of buildings -- Environmental labelling of buildings.
Keywords: Buildings -- Environmental engineering; Energy policy; Energy and state; Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Renewable energy sources; Building Physics, HVAC; Energy Policy, Economics and Management; Engineering Thermodynamics, Heat and Mass Transfer; Renewable Energy